1987
DOI: 10.1159/000195216
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Ciprofloxacin in the Elderly

Abstract: The pharmacokinetics of ciprofloxacin, administered orally as a 250-mg tablet were compared in 10 young (age 20–30 years) and 10 elderly (age 60–73 years) healthy volunteers. The time to peak serum concentrations was about 80 min in both age groups, although the maximum concentration attained was significantly greater in the old (1.7mg/l) than the young (1.2 mg/l). Area under the plasma concentration-time curve, corrected for body weight, was on average 48% greater in the elderly, but the mean terminal elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
21
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 8 publications
4
21
1
Order By: Relevance
“…No significant differences were noted between the first dose and steady-state pharmacokinetic parameters, with the exception of an increase in the apparent volume of distribution. The results were consistent with previous studies in healthy and mildly ill elderly subjects undergoing assessment after single doses of oral ciprofloxacin in that the maximum concentration of drug in serum (Cmax) and area under the concentration-time curve (AUC) were increased compared with those of young volunteers receiving the same doses (2,3,5,9,11,15).These studies suggest that the pharmacokinetics of ciprofloxacin are altered in elderly subjects. However, comparative intravenous and oral ciprofloxacin pharmacokinetic parameters during maintenance dose therapy in the elderly have not been evaluated.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…No significant differences were noted between the first dose and steady-state pharmacokinetic parameters, with the exception of an increase in the apparent volume of distribution. The results were consistent with previous studies in healthy and mildly ill elderly subjects undergoing assessment after single doses of oral ciprofloxacin in that the maximum concentration of drug in serum (Cmax) and area under the concentration-time curve (AUC) were increased compared with those of young volunteers receiving the same doses (2,3,5,9,11,15).These studies suggest that the pharmacokinetics of ciprofloxacin are altered in elderly subjects. However, comparative intravenous and oral ciprofloxacin pharmacokinetic parameters during maintenance dose therapy in the elderly have not been evaluated.…”
supporting
confidence: 90%
“…Although the apparent volume of distribution or renal clearance was not reported, the pharmacokinetic differences were attributed to altered volume of distribution or increased bioavailability with aging. Similar conclusions were reported by Bayer et al (3). LeBel et al (15) also reported significantly higher ciprofloxacin concentrations in serum but observed a twofold increase in the ciprofloxacin elimination half-life of healthy elderly subjects compared with that of young volunteers after a single 500-mg oral dose.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…For ketoconazole, this CI was chosen because a change in exposure of ketoconazole by as much as 59% when taken with food does not appear to be of clinical relevance since the package insert does not provide guidance for administration with regard to meal (7). For ciprofloxacin, this CI was chosen because no adjustment of ciprofloxacin dose is required for elderly subjects despite an increase in exposure by 48% in the elderly compared to young adults (2). Only descriptive statistics were determined for the T max and T 1/2 values of indinavir, ketoconazole, and ciprofloxacin and for all pharmacokinetic parameters for didanosine.…”
Section: Methodsmentioning
confidence: 99%
“…Because renal function and various metabolic clearance mechanisms decrease with age (13), the pharmacokinetics of amifloxacin may be different in the elderly than it is in younger subjects. Indeed, other fluoroquinolone agents, such as ciprofloxacin, ofloxacin, and pefloxacin, have demonstrated remarkable reductions in renal clearance in the elderly compared with clearance in younger volunteers (1,3,10). Furthermore, this change in metabolism may predispose the elderly to the development of adverse drug reactions, a phenomenon already suggested for ofloxacin (9).…”
mentioning
confidence: 99%